2021
DOI: 10.1186/s12903-021-01831-6
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of COVID-19 vaccination and its determinants among Lebanese dentists: a cross-sectional study

Abstract: Background Dentists are at high risk of exposure to occupational Coronavirus Disease 2019 (COVID-19). Since vaccination is crucial to control COVID-19 pandemic, we aimed to assess COVID-19 vaccination acceptance and its determinants among Lebanese practicing dentists. Methods A cross-sectional online study was conducted between February 15 and 22, 2021, among dentists practicing in Lebanon. Prevalence of COVID-19 vaccine acceptance was estimated. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 27 publications
7
51
2
Order By: Relevance
“…This rapidly achieved process was surrounded by many rumors and conspiracy theories, which consequently resulted in high rates of vaccine hesitancy. There are many reports, from almost all Arab countries, confirming that the fear of serious post-vaccination side effects and complications is the main reason behind the high rates of vaccine hesitancy [ 18 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. In this study, a high rate of vaccine hesitancy (51%) was reported among the participants before receiving a vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rapidly achieved process was surrounded by many rumors and conspiracy theories, which consequently resulted in high rates of vaccine hesitancy. There are many reports, from almost all Arab countries, confirming that the fear of serious post-vaccination side effects and complications is the main reason behind the high rates of vaccine hesitancy [ 18 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. In this study, a high rate of vaccine hesitancy (51%) was reported among the participants before receiving a vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…The low public acceptability of COVID-19 vaccines is most probably associated with rumors and conspiracy theories [ 20 ]. Reports from several Arab countries have shown that fear of serious post-vaccination side effects and misinformation about COVID-19 vaccines are the biggest obstacles facing mass vaccination campaigns [ 18 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Hence, this could result in delaying vaccination and waning immunity against SARS-CoV-2 over time, after initial infection or vaccination [ 35 ], and subsequently, it may prolong the burden of the COVID-19 pandemic in the region.…”
Section: Introductionmentioning
confidence: 99%
“…In an Italian study, 18% of dentists opposed vaccination [ 40 ]. In an online survey in February among 529 dentists in Lebanon, 86% reported that they were willing to receive or already received a COVID-19 vaccine [ 41 ]. Only about 21% of Egyptian HCWs accepted to be COVID-19 vaccinated [ 42 ]; in a survey in the United States, only 64.6% of medical professionals accepted the COVID-19 vaccine [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, these studies usually included smaller numbers of participants compared to ours. Nasr et al conducted an online survey involving 529 Lebanese dentists between 15 and 22 February 2021 [ 11 ]. A total of 86% of participants were willing to receive or have already received a COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Although dentists are one of the most vulnerable occupational groups, information about COVID-19 vaccination among them is scarce. There is only a very limited amount of works on this topic, and in the vast majority, it only concerns the willingness, hesitancy, or acceptance of dentists to get vaccinated [ 11 , 12 , 13 , 14 , 15 ]. To the best of our knowledge, this is the first study to provide data on real COVID-19 vaccination among dental professionals.…”
Section: Introductionmentioning
confidence: 99%